1996
DOI: 10.1002/cjce.5450740509
|View full text |Cite
|
Sign up to set email alerts
|

The non‐linear behaviour of the NO‐H2 reaction over Rh surfaces

Abstract: In this paper we describe the non-linearity of the NO-H, reaction over Rh surfaces. Rate oscillations have been observed over a stepped (1 1 1) surface with (100) steps, (Rh(533) at low pressures ( I @ Pa) below 500 K, while no oscillations could be observed under these conditions over a Rh( 100) surface and a stepped (1 00) surface with ( 1 1 I ) steps, Rh(71 I). The thermal stability of the N atoms formed during the reaction explains the observed structure sensitivity. Moreover, the results suggest that diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Based on the FEM studies reported by van Tol et al a number of large Rh single-crystal surfaces (0.5 cm 2 ) consisting of ( 111) and (100) terraces were selected by Janssen et al [67,68,76] and Cobden et al [66].…”
Section: Kinetic Rate Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the FEM studies reported by van Tol et al a number of large Rh single-crystal surfaces (0.5 cm 2 ) consisting of ( 111) and (100) terraces were selected by Janssen et al [67,68,76] and Cobden et al [66].…”
Section: Kinetic Rate Oscillationsmentioning
confidence: 99%
“…TDS shows that N ads atoms start to combine and desorb between 450 and 600 K from Rh(533) [67]. In contrast, Rh(100) is deactivated in this temperature range due to the formation of a c(2 × 2)-N adlayer that is stable up to 700 K [67,76,77]. Strongly bound N ads atoms also form on the four-atom wide (100) terraces of Rh(410) and Rh(711) and, accordingly, no rate oscillations were observed over these surfaces either.…”
Section: The Role Of Surface Structurementioning
confidence: 99%